EFISIENSI TEKNIS USAHA TANI PADI DI DESA MEUNASAH PANTON LABU KECAMATAN TANAH JAMBO AYE KABUPATEN ACEH UTARA - mutia fhazira; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to analyze the technical efficiency of rice farming in Desa Meunasah Panton Labu, Tanah Jambo Aye Sub-district, North Aceh Regency. This study uses primary data obtained from the distribution of questionnaires to 50 respondents who are landowners and farmers in Desa Meunasah Panton Labu, Tanah Jambo Aye Sub-district, North Aceh Regency. This study used is the Purposive sampling method. Data Envelopment Analysis (DEA) is used to analysis the data. The results showed that the landowners were more technically efficient than sharecroppers where the number of farmers who had reached the level of efficiency as many as 19 respondents.